On the analysis of magnetohydrodynamics and magnetic field-dependent viscosity effects on thermogravitational convection of hybrid nanofluid in an enclosure with curved walls - Pandit, Swapan K.; Goswami, Krishno D.; Chattopadhyay, Anirban; Öztop, Hakan Fehmi (Aip Publishing, 2021)
This work deals with the impact of magnetic field-dependent viscosity and magnetohydrodynamics on the natural convection heat transfer of Ag-MgO (50%-50%) water hybrid nanoliquid in a complicated enclosure. The considered cavity with concave or convex horizontal boundaries has been differentially heated and cooled by multiple heat sources and heat sinks. The governing equations (Navier-Stokes equations) constituting stream function (psi)-vorticity (zeta) formulation with energy equation are solved by adopting a compact finite difference scheme. Meanwhile, the flow domain that is influenced by several factors including Hartmann number (0 <= Ha <= 60), hybrid nanoparticles volume fraction (0 <= phi(hnp) <= 0.02), Rayleigh number (10(3) <= Ra <= 10(6)), orientation angle of magnetic field (0(0) <= gamma <= 90(0)), magnetic number (0 <= delta(0) <= 1), different cases (Case-I to III), and internal heat generation or absorption (-2 <= Q <= 2) is analyzed generously. Experimentally based correlations for thermal conductivity and dynamic viscosity have been used throughout the study. The outcomes show that the geometric parameters can be used as an excellent controller of the thermal performance inside the wavy chamber. Published under an exclusive license by AIP Publishing.
Keywords: Transient Natural-Convection; Heat-Transfer; Entropy Generation; Mixed Convection; Square Cavities; Compact Scheme; Fluid-Flow; Nanoliquid; Simulation; Channel